2019
DOI: 10.1186/s13049-019-0668-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management of splenic injury in closely monitored patients with reduced consciousness is safe and feasible

Abstract: BackgroundTreatment of blunt splenic injury has changed over the past decades. Nonoperative management (NOM) is the treatment of choice. Adequate patient selection is a prerequisite for successful NOM. Impaired mental status is considered as a relative contra indication for NOM. However, the impact of altered consciousness in well-equipped trauma institutes is unclear. We hypothesized that impaired mental status does not affect outcome in patients with splenic trauma.MethodsOur prospectively composed trauma da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Current medical advancements encourage minimal invasive procedures to control hemorrhage [ 35 ]. An increasing number of traumatic hepatic and splenic injuries are treated non-operatively [ 36 , 37 ] or with the support of interventional radiology (e.g., coiling) [ 38 , 39 ]. With evolving minimally invasive techniques or the non-operative treatment of solid organ lesions, there might be a higher threshold for the indication to perform damage-control laparotomy [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current medical advancements encourage minimal invasive procedures to control hemorrhage [ 35 ]. An increasing number of traumatic hepatic and splenic injuries are treated non-operatively [ 36 , 37 ] or with the support of interventional radiology (e.g., coiling) [ 38 , 39 ]. With evolving minimally invasive techniques or the non-operative treatment of solid organ lesions, there might be a higher threshold for the indication to perform damage-control laparotomy [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOM was demonstrated to be feasible also in patients with altered consciousness: Teuben et al reported their retrospective experience with NOM in 20 patients with GCS < 14. All the patients were admitted to a monitored intermediate care unit or ICU and underwent frequent examinations of vital signs and physical examinations (including hemoglobin level measurements) [ 79 ]. Recently, Kumar et al published a randomized trial where patients treated with NOM for blunt spleen and liver trauma were randomized to early (3 days) or late (5 days) discharge.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 90 could be treated by NOM. There were 7 patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), p = 0.019) and a higher lactate (2.1 (1.7-3.6) vs. 4.1(2.7-5.4), p = 0.016) than patients with high grade injuries treated by spleen preserving treatment. All of the patients with a high grade splenic injury in the splenectomy group were hemodynamically unstable, this was visible by significant more transfusion requirements of ECs (p = 0.005), FFP's (p < 0.014) and thrombocytes (p < 0.013).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…However, Spleen preservation is not always an option since it can lead to life-threatening hemorrhages [11]. The most important prerequisite for successful NOM is adequate patient selection [12][13][14][15]. Hence, it is of utmost importance to choose the right management for the right patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation